„Niewinne” – od postulatu dziewczęcości do inicjacji w poezji kobiet - Sołtys-Lewandowska, Edyta (Poznańskie Studia Polonistyczne. Seria Literacka, 2018)
The article explores pictures of “a little girl” and of sexual initiation in 20th and 21st-century Polish women’s poetry, especially by Wisława Szymborska, Barbara Klicka, Jolanta Nawrot, Wioletta Grzegorzewska i Małgorzata Lebda. The girlhood showed in their poems is a certain potentiality of womanhood, often imbued with ripening eroticism very difficult to control. At the same time the girlhood is entangled in schematism of potential scenarios destined for a women subject: personal dependence and sense of being dominated, escape or emancipation. Initiatory poems show rather strong dependence on archetypical (The Little Match Girl) and mythicizing conventions of describing adolescence, still they can present idiomatic construction of female identity.